Chatter alleviation for a class of second-order under-actuated mechanical systems with matched and mismatched disturbances. (February 2017) - Shi, Jinjin; Wang, Jinxiang; Fu, Fangfa
The chattering phenomenon and a system with both matched and mismatched disturbances are the major difficulties in sliding mode control design. This paper presents an effective design procedure to alleviate these two difficulties for a class of second-order under-actuated mechanical systems. In the proposed design, new hierarchical sliding surfaces are designed and a modified disturbance observer is utilized to estimate the lumped disturbance which is a linear combination of the matched and mismatched disturbances. The chatter in control input is filtered out by an integrator, which acts as a low-pass filter. The asymptotic stabilities of the entire sliding surfaces are guaranteed. A design study considering lateral control of a vehicle with matched and mismatched disturbances demonstrates the effectiveness of the proposed design.